Analysis of RET promoter CpG island methylation using methylation-specific PCR (MSP), pyrosequencing, and methylation-sensitive high-resolution melting (MS-HRM): impact on stage II colon cancer patient outcome. Issue 1 (December 2016) - Draht, Muriel; Smits, Kim; Jooste, Valérie; Tournier, Benjamin; Vervoort, Martijn; Ramaekers, Chantal; Chapusot, Caroline; Weijenberg, Matty; van Engeland, Manon; Melotte, Veerle
Abstract Background Already since the 1990s, promoter CpG island methylation markers have been considered promising diagnostic, prognostic, and predictive cancer biomarkers. However, so far, only a limited number of DNA methylation markers have been introduced into clinical practice. One reason why the vast majority of methylation markers do not translate into clinical applications is lack of independent validation of methylation markers, often caused by differences in methylation analysis techniques. We recently describedRET promoter CpG island methylation as a potential prognostic marker in stage II colorectal cancer (CRC) patients of two independent series. Methods In the current study, we analyzed theRET promoter CpG island methylation of 241 stage II colon cancer patients by direct methylation-specific PCR (MSP), nested-MSP, pyrosequencing, and methylation-sensitive high-resolution melting (MS-HRM). All primers were designed as close as possible to the same genomic region. In order to investigate the effect of different DNA methylation assays on patient outcome, we assessed the clinical sensitivity and specificity as well as the association ofRET methylation with overall survival for three and five years of follow-up. Results Using direct-MSP and nested-MSP, 12.0 % (25/209) and 29.6 % (71/240) of the patients showedRET promoter CpG island methylation. Methylation frequencies detected by pyrosequencing were related to the threshold for positivity that definedRET methylation. Methylation frequencies obtained by pyrosequencing (threshold for positivity at 20 %) and MS-HRM were 13.3 % (32/240) and 13.8 % (33/239), respectively. The pyrosequencing threshold for positivity of 20 % showed the best correlation with MS-HRM and direct-MSP results. Nested-MSP detectedRET promoter CpG island methylation in deceased patients with a higher sensitivity (33.1 %) compared to direct-MSP (10.7 %), pyrosequencing (14.4 %), and MS-HRM (15.4 %). WhileRET methylation frequencies detected by nested-MSP, pyrosequencing, and MS-HRM varied, the prognostic effect seemed similar (HR 1.74, 95 % CI 0.97–3.15; HR 1.85, 95 % CI 0.93–3.86; HR 1.83, 95 % CI 0.92–3.65, respectively). Conclusions Our results show that upon optimizing and aligning fourRET methylation assays with regard to primer location and sensitivity, differences in methylation frequencies and clinical sensitivities are observed; however, the effect on the marker's prognostic outcome is minimal.